Proceedings of the Third International Symposium on Materials and Sustainable Development - Abdelbaki, Benmounah; Safi, Brahim; Saidi, Mohammed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the proceedings of The third International Symposium on Materials and Sustainable Development. This 2-days Conference was organized by the Research Unit: Materials, Processes and Environment and M'hamed Bougara at the University of Boumerdes, Algeria. The papers present topics on materials, processes and environment aspects, covering the latest results on materials and sustainable development research in Algeria and worldwide.
Advanced materials and Nanotechnology -- Materials Chemistry and Building Materials -- Waste Management, Recycling and Environment -- Materials Processing Technology.
Keywords: Materials science; Sustainability; Building materials; Materials Science; Sustainability; Building Materials